Metalinguagem como tecnologia cognitiva em textos de divulgação científica - Silva, Carlos Eduardo da (2019)
The object of this dissertation is the metalanguage as cognitive technology in texts of scientific diffusion in the Linguistics field. The research aims to show how elements of metalanguage appear in texts of scientific diffusion in this field and their role in making accessible the knowledge and the concepts that circulate in the academic environment to a larger audience. theoretical foundations are based in the notions of “language as cognitive technology” proposed by Marcelo Dascal (2002, and “language as constitutive activity” assumed by Carlos Franchi (2011). We also take into account some considerations on scientific culture developed by Carlos Vogt (2012). The methodology applied was the quantitative and qualitative analysis in a corpus composed by 47 texts. Results allow us to say that: i) semantic indetermination works as a tool for the (re)definition of theoretical terms; ii) that traditional grammar has a fundamental role in texts of scientific diffusion in linguistics, either in the definition of technical terms or as a basis for the establishment of the themes discussed in the texts; and iii) epilinguistic activity is a tool for metalinguistic activity.